ANALISIS PERHITUNGAN PPH PASAL 21 TERHADAP PEGAWAI TETAP ATAS BERLAKUNYA PMK RI NO: 101/PMK.010/2016 TENTANG PTKP STUDI KASUS PADA PT. BANK SULUTGO CABANG TAHUNA - Pangandaheng, Vinry Y; Elim, Inggriani; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Tax is a compulsory contribution to a country that is indebted by an individual or a coercive body under the Act, without obtaining direct remuneration and being used for the purposes of the state to the greatest possible prosperity of the people. This study aims to find out and analyze the calculation of income tax (PPh) article 21 on permanent employees on the enactment of new regulations PMK No: 101 / PMK.010 / 2016 in the interest of tax payments efficiently in PT. Bank SulutGo Tahuna Branch. This research uses descriptive method with qualitative approach. Based on the results of research, it is concluded that the calculation and reporting of Article 21 Income Tax at PT. Bank SulutGo Branch Tahuna has been in accordance with the Law No. 36 of 2008 and the procedures set forth in the Tax Regulations applicable in Indonesia, and PT. Bank SulutGo Branch Tahuna has done the calculation of PTKP in accordance with Regulation of the Minister of Finance of the Republic of Indonesia No: 101 / PMK.010 / 2016.Key Words : Calculation, Income Tax Article 21, PMK No: 101 / PMK.010 / 2016